Perkembangan Islam Di Kesultanan Palembang Darussalam Tahun 1659-1821 - Abu Soli; Ira Miyarni Sustianingsih; Sarkowi Sarkowi (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2022)
This study aims to describe the development of Islam in the Sultanate of Palembang Darussalam in 1659-1821. This study uses the historical method with four steps, namely heuristics, verification, interpretation and historiography. The results of the study explain the beginning of development. In the 17th century Islam then began to experience development as evidenced by the establishment of mosques as places of worship and religious studies and various religious activities began to appear. The peak of the development of Islam occurred in the 18th century until the 19th century, at that time the Sultanate of Palembang Darussalam experienced a tradition of intellectual awakening in the field of Islam and Malay literature. The conclusion of this study is that the development of Islam began with the formation of an Islamic-style government, then Islam began to spread widely to the uluan area, which is around the Ogan River and the Komering River. This development is inseparable from the contribution of local scholars, one of which is Abdus Shomad al-Palimbani. Keywords: Development, Islam, Palembang Darussalam Sultanate.